Effect of heavy metals on the growth and development of sweet sorghum (Experimental biology, 2015)
The paper describes the comparative study of the effect of different concentrations of heavy metal salts (plumbumand copper) on the germination and growth of plants of sweet sorghum. Toxic effects of heavy metals on plant growth atearly stage of development have been determined. Strong toxic effects of heavy metals on the root system than the shootof plants have been shown. Storage material of seeds more sensitive to lead than copper has been defined.
Keywords: һeavy metals; copper; lead; sorghum; biomass; germination; growth.